Leader Humor and Employee Job Crafting: The Role of Employee-Perceived Organizational Support and Work Engagement - Tan, Ling; Wang, Yongli; Qian, Wenjing; Lu, Hailing (Frontiers in Psychology, 2020)
Research on the outcomes of leader humor has mainly focused on attitudinal or in-role behaviors, while proactive change-oriented behaviors has been neglected. Addressing these issues is important for scholars and practitioners to better understand how leader humor enables subordinates to behave proactively. By integrating the resource accumulation perspective and the motivational process of the Job Demands-Resources (JD-R) model, we frame leader humor as a socioemotional resource that can help employees to create other forms of resources, such as job resources (i.e., perceived organizational support). In turn, these job resources relate to employees’ motivations (i.e., work engagement) and behaviors (i.e., job crafting). We predict that leader humor is positively related to seeking resources and challenges and negatively associated with reducing demands through the serial mediating effects of followers’ perceived organizational support and work engagement. We test these hypotheses using an experimental design with a field sample in Study 1. Furthermore, we strengthen our hypotheses by replicating our results through a multiwave field study in Study 2. We consistently find: (1) a positive association between leader humor and followers’ perceived organizational support; (2) a positive link between followers’ perceived organizational support and work engagement; and (3) serial mediating effects of followers’ perceived organizational support and work engagement on the leader humor-job crafting link. The implications of the findings and future directions for research investigating leader humor and job crafting are discussed.